The modern portrait poem : from Dante Gabriel Rossetti to Ezra Pound - Dickey, Frances, 1970- (University of Virginia Press, 2012)
"In The Modern Portrait Poem, Frances Dickey recovers the portrait as a poetic genre from the 1860s through the 1920s. Combining literary and art history, she examines the ways Dante Gabriel Rossetti, Algernon Swinburne, and J.M. Whistler transformed the genre of portraiture in both painting and poetry. She then shows how their new ways of looking at and thinking about the portrait subject migrated across the Atlantic to influence Ezra Pound, T.S. Eliot, William Carlos Williams, Amy Lowell, E.E. Cummings, and other poets. These poets creatively exposed the Victorian portrait to new influences ranging from Manet's realism to modern dance, Futurism, and American avant-garde art. They also condensed, expanded, and combined the genre with other literary modes including epitaph, pastoral, and Bildungsroman. Dickey challenges the tendency to view Modernism as a break with the past and as a transition from aural to visual orientation. She argues that the Victorian poets and painters inspired the new generation of Modernists to test their vision of Aestheticism against their perception of modernity and the relationship between image and text. In bridging historical periods, national boundaries, and disciplinary distinctions, Dickey makes a case for the continuity of this genre over the Victorian/Modernist divide and from Britain to the United States in a time of rapid change in the arts."--Project Muse